Calidad del servicio a los usuarios de la cooperativa de transporte escolar e institucional Oswaldo Guayasamín de la Ciudad de Guayaquil. - Quevedo Trujillo, Bryan Stiven (2022)
The present investigation was carried out in the context of the Oswaldo Guayasamin School and Institutional Transport Cooperative, in the province of Guayas, in the canton of Guayaquil. The same that is dedicated exclusively to the provision of transportation service, both school and institutional. The main objective of this research work was to analyze the quality of the service provided by the Oswaldo Guayasamin School and Institutional Transportation Cooperative. For the purposes of the investigation, a descriptive methodology with a qualitative-quantitative approach was used, since an interview was applied to the manager of the cooperative and a survey of users. Among the main results found, it was established that 95% of them consider that the service provided is good, 100% of them feel safe to move in their six buses with a capacity of 48 passengers, also for 100% of the informants, their main condition is to have a punctual transportation service. This research is based on what is established by the Commerce Career of the Faculty of Administration, Finance and Information Technology, for which the line of research was applied: Financial Management, administrative, tax, audit, control. In the same way, since it is a private company that is analyzed, the research subline is involved: Companies and public and private institutions.